2000
DOI: 10.1029/1999jd901040
|View full text |Cite
|
Sign up to set email alerts
|

Low‐ozone events and three‐dimensional transport at midlatitudes of South America during springs of 1996 and 1997

Abstract: Abstract.Sudden and transient decreases of ozone column values were detected over the midlatitudes of South America during the springs of 1996 and 1997 by a network of ground instruments. These low-ozone events were accompanied by air temperature decreases in the lower stratosphere. The analysis of the events suggests a connection with the springtime Antarctic ozone hole. Three-dimensional isentropic back trajectories showed that vertical motion also contributed to the decreases of total ozone observed at the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 18 publications
(1 reference statement)
2
15
0
6
Order By: Relevance
“…Similar events of low ozone air masses intrusions from Antarctic ozone hole toward mid latitude like those analyzed here were also observed over South America (Kirchho et al, 1996;Perez et al, 2000), Southern Africa (Semane et al, 2006) and New Zealand (Brinksma et al, 1998). …”
Section: Discussionsupporting
confidence: 86%
“…Similar events of low ozone air masses intrusions from Antarctic ozone hole toward mid latitude like those analyzed here were also observed over South America (Kirchho et al, 1996;Perez et al, 2000), Southern Africa (Semane et al, 2006) and New Zealand (Brinksma et al, 1998). …”
Section: Discussionsupporting
confidence: 86%
“…Perez et al, 2000;Pinheiro et al, 2012, as well as the identification of the existence of a connection between the transport of air masses in the stratosphere and the troposphere weather condition, mainly by the performance of the tropospheric jet stream, where its displacement influence the vertical distribution of ozone content (Bukin et al 2011) and causes intrusion of stratospheric air into the troposphere (Stohl et al, 2003). Moreover, on the South of Brazil, similar to the way the present study, this type of event has occurred after the passage of a frontal system .…”
Section: Discussionmentioning
confidence: 99%
“…The passage of air masses originating from the Antarctic ozone hole (Farman et al, 1985) on medium latitudes was first observed on the South of Brazil (29.4ºS; 53.8ºW) by Kirchhoff et al (1996), being this type of phenomenon called 'influence of the Antarctic ozone hole, which has been frequently observed over South America (Perez et al, 2000;Pinheiro et al, 2012). Peres et al, 2012, observed …”
Section: Introductionmentioning
confidence: 99%
“…Este tipo de fenômeno vem sendo frequentemente observado sobre o Sul da América do Sul (Perez e Jaque, 1998;Perez et al, 2000, Paznino et al, 2008, Sul do Brasil , Sul do continente africano (Semane et al, 2006;Sivakumar et al, 2007) e Nova Zelândia (Brinksma et al, 1998).…”
unclassified